Differentiation between severe HELLP syndrome and thrombotic microangiopathy, thrombotic thrombocytopenic purpura and other imitators. (June 2015) - Pourrat, O.; Coudroy, R.; Pierre, F.
Abstract: Pre-eclampsia complicated by severe HELLP (hemolysis, elevated liver enzymes and low platelet count) syndrome is a multi-organ disease, and can be difficult to differentiate from thrombotic microangiopathy (appearing as thrombotic thrombocytopenic purpura or hemolytic uremic syndrome), acute fatty liver, systemic erythematous lupus, antiphospholipid syndrome and severe sepsis. Many papers have highlighted the risks of misdiagnosis resulting in severe consequences for maternal health, and this can be fatal when thrombotic thrombocytopenic purpura is misdiagnosed as severe HELLP syndrome. The aim of this paper is to propose relevant markers to differentiate pre-eclampsia complicated by severe HELLP syndrome from its imitators, even in the worrying situation of apparently indistinguishable conditions, and thereby assist clinical decision-making regarding whether or not to commence plasma exchange. Relevant identifiers to establish the most accurate diagnosis include the frequency of each disease and anamnestic data. Frank hemolysis, need for dialysis, neurological involvement and absence of disseminated intravascular coagulation are indicative of thrombotic microangiopathy. The definitive marker for thrombotic thrombocytopenic purpura is undetectable ADAMTS 13 activity.